Pengaruh Supervisi Akademik, Keterampilan Manajerial Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru SD Negeri di Kecamatan Bulu Kabupaten Temanggung - Riyadi, Fifin Agus; Kusumaningsih, Widya; Ginting, Rosalina Br. (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Teacher performance refers to the ability possessed by a teacher to carry out quality teaching activities. Academic supervision, principal managerial skills, and work motivation play a role in improving teacher performance. The aims of this research are (1) to determine the influence of academic supervision on teacher performance, (2) to determine the influence of the principal's managerial skills on teacher performance, (3) to determine the influence of work motivation on teacher performance, (4) to determine the influence of academic supervision and the principal's managerial skills , and work motivation simultaneously on teacher performance. The population in this study were all state elementary school teachers in Bulu District, Temanggung Regency, totaling 174 people with a research sample of 121 people. The data collection method uses a questionnaire. Data analysis uses descriptive analysis, prerequisite tests, hypothesis testing, and regression testing with the help of the SPSS 26 for Windows computer application. The results of the research show (1) there is a positive and significant influence of academic supervision on the performance of public elementary school teachers in Bulu District, Temanggung Regency, which isexpressed by the regression equation Ŷ = a + bX1, namely Ŷ = 46.795 + (0.387)X1, with a contribution of 43.7% ; (2) there is a positive and significant influence of the principal's managerial skills on the performance of public elementary school teachers in Bulu District, Temanggung Regency, which is expressed by the regression equation Ŷ = 59.269 + (0.277)X2 with a contribution of 21.1%; (3) there is a positive and significant influence of work motivation on the performance of state elementary school teachers in Bulu District, Temanggung Regency, which is expressed by the regression equation Ŷ = 49.975 + (0.338)X3, with a contribution of 34.2%; (4) there is a positive and significant influence of academic supervision, principal managerial skills, and work motivation simultaneously on teacher performance which is expressed by the regression equation Ŷ = 15.241 + 0.275X1 + 0.121X2 + 0.220X3, with a contribution of 62.5%. Keywords: Academic Supervision, Principal Managerial Skills, Work Motivation, Teacher Performance